Pharmacological characterization of a novel centrally permeable P2X7 receptor antagonist: JNJ‐47965567. (17th September 2013) - Bhattacharya, Anindya; Wang, Qi; Ao, Hong; Shoblock, James R; Lord, Brian; Aluisio, Leah; Fraser, Ian; Nepomuceno, Diane; Neff, Robert A; Welty, Natalie; Lovenberg, Timothy W; Bonaventure, Pascal; et al.
Abstract : Background and Purpose: An increasing body of evidence suggests that the purinergic receptor P2X, ligand‐gated ion channel, 7 (P2X7) in the CNS may play a key role in neuropsychiatry, neurodegeneration and chronic pain. In this study, we characterized JNJ‐47965567, a centrally permeable, high‐affinity, selective P2X7 antagonist. Experimental Approach: We have used a combination of in vitro assays (calcium flux, radioligand binding, electrophysiology, IL‐1β release) in both recombinant and native systems. Target engagement of JNJ‐47965567 was demonstrated by ex vivo receptor binding autoradiography and in vivo blockade of Bz‐ATP induced IL‐1β release in the rat brain. Finally, the efficacy of JNJ‐47965567 was tested in standard models of depression, mania and neuropathic pain. Key Results: JNJ‐47965567 is potent high affinity (pKi 7.9 ± 0.07), selective human P2X7 antagonist, with no significant observed speciation. In native systems, the potency of the compound to attenuate IL‐1β release was 6.7 ± 0.07 (human blood), 7.5 ± 0.07 (human monocytes) and 7.1 ± 0.1 (rat microglia). JNJ‐47965567 exhibited target engagement in rat brain, with a brain EC50 of 78 ± 19 ng·mL −1 (P2X7 receptor autoradiography) and functional block of Bz‐ATP induced IL‐1β release. JNJ‐47965567 (30 mg·kg −1 ) attenuated amphetamine‐induced hyperactivity and exhibited modest, yet significant efficacy in the rat model of neuropathic pain. No efficacy was observed in forced swim test. Conclusion and Implications: JNJ‐47965567 is centrally permeable, high affinity P2X7 antagonist that can be used to probe the role of central P2X7 in rodent models of CNS pathophysiology.